Southern California and the perfect drought: Simultaneous prolonged drought in southern California and the Sacramento and Colorado River systems - MacDonald, Glen M. (2008)
Southern California relies heavily upon imported water from the Sacramento and Colorado river systems to augment local supplies and to mitigate the impacts of drought. In this paper a ‘perfect drought’ is defined as a prolonged drought that affects southern California, the Sacramento River basin and the upper Colorado River basin simultaneously. Examination of instrumental climate and discharge records shows that over the past century such perfect droughts do occur, but generally persist for less than five years. Perfect droughts that extend across all three areas are associated with anomalous upper-level high pressure off west coast and over western North America which is in turn associated with anomalously cool eastern Pacific sea surface temperatures. Exploratory dendrochronological reconstructions of winter Palmer Drought Severity in southern California, annual discharge of the Sacramento River and annual discharge of the Colorado River demonstrate that prolonged perfect droughts (∼30–60 years), which produced arid conditions in all three regions simultaneously, developed in the mid-11th century and the mid-12th century during the period of the so-called ‘Medieval Climate Anomaly’. Prolonged aridity in western North America during this period appears to have been associated with cooling of the eastern equatorial and North Pacific related to the differential thermal response of the western and eastern Pacific to increased tropical radiative forcing at that time. This potential linkage between positive radiative forcing and prolonged perfect droughts raises serious concerns regarding the hydrological impacts of future climate warming in southern California and the West.